Cardiac Magnetic Resonance Angiography using Blood-Pool Contrast Agents: Comparison of Citrate-Coated Very Small Superparamagnetic Iron Oxide Particles with Gadofosveset Trisodium in Pigs - Schnorr, J.; Taupitz, M.; Schellenberger, E. A.; Warmuth, C.; Fahlenkamp, U. L.; Wagner, S.; Kaufels, N.; Wagner, M. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2012)
Purpose: To compare citrate-coated very small superparamagnetic iron oxide particles (VSOP) with gadofosveset trisodium as blood pool contrast agents for cardiac magnetic resonance angiography (CMRA) in pigs. Materials and Methods: Animal experiments were approved by the responsible authority. 10 CMRA-like examinations were performed at 1.5 T after administration of VSOP (0.06 mmol Fe/kg; 5 examinations) and gadofosveset trisodium (0.03 mmol Gd/kg; 5 examinations). The CMRA protocol included ECG-gated inversion-recovery-prepared T1-weighted gradient echo imaging (IR-GRE; one slice) and ECG-gated inversion recovery prepared steady state free precession imaging (IR SSFP; one slice) before and 1, 3, 5, 10, 15, 20, 25, 30, 40, 50, and 60 min after injection. At each time point, three different inversion times (TI; 200 msec, 300 msec, and 400 msec) were applied. Contrast-to-noise ratios (CNR) between blood and myocardium were calculated and compared using mixed linear models. Results: No significant differences of CNR were found between IR-GRE and IR SSFP. At 3 and 5 min after contrast agent administration, VSOP showed a significantly higher CNR than gadofosveset trisodium when TI of 200 msec and 300 msec were applied (TI of 200 msec at 3 min: 8.2 ± 0.7 vs. 5.4 ± 0.7; TI of 200 msec at 5 min: 7.9 ± 0.7 vs. 3.5 ± 0.8; TI of 300 msec at 3 min: 11.7 ± 0.7 vs. 8.8 ± 0.8; TI of 300 msec at 5 min: 11.4 ± 0.7 vs. 8.0 ± 0.8; p < 0.05). Moreover, significant differences in favor of VSOP were found for all time points from 10 to 40 min irrespective of TI (p < 0.05). Conclusion: VSOP has superior blood-pool properties compared to gadofosveset trisodium resulting in prolonged improvement of CNR on CMRA.
Keywords: experimental study; contrast agents; heart; blood vessels